Risk-Based Budgeting in Non-Profit Organization (A Case Study at Rumah Amal Salman) - Afifah Shafari Zuliansyah; Oktofa Yudha Sudrajad (Utan Kayu Publishing, 2025)
This study aims to propose a risk-based budgeting framework for non-profit organizations, particularly zakat institutions, with a case study at Rumah Amal Salman (RAS). This study was conducted because there is no integration between risk management and the budgeting process. As a result, risk management is only administrative in nature, and the programs developed do not consider the uncertainties that may occur systematically. The method used in this study is a qualitative approach combined with financial and budget analysis. Data was collected through various documents such as financial reports, work plan and budget documents (RKA), internal risk analysis documents, and through unstructured interviews with a key internal informant of the institution. Data was analyzed through two approaches, such as financial analysis and risk analysis. Financial analysis was conducted through financial ratio analysis and trend analysis. Risk data was analyzed through a risk management process adapted from elements of ISO 31000. This process yielded several findings. First, most of the risks were found in the Program and Marketing Department. In terms of risk categories, the majority were compliance, strategic, and operational risks. Second, the results of mapping risk mitigation action into program proposals indicate that RAS needs to prioritize programs focused on system and database development. This finding aligns with the results of the analysis from the opposite direction, where identified risks are mapped into budgeted programs. This demonstrates the consistency of the need to strengthen digital systems as a strategic step in risk control. Finally, this study generates a risk-based budgeting framework and workflow that can be implemented as a standard operating procedure (SOP) or budget planning flowchart. In general, the proposed budget planning process flow is similar to the existing one. Previously, the process began with the establishment and targeting of budget allocations. Now, two additional processes have been added before that, running in parallel, such as reviewing previous financial performance and reviewing, updating, and establishing risk profiles.